The promise of pulsed field ablation and the challenges ahead - Iyengar, Shruti Krishna; Iyengar, Sumedh; Srivathsan, Komandoor (Frontiers in Cardiovascular Medicine, 2023)
For many years, guidelines have suggested thermal ablation for the treatment of atrial fibrillation. Thermal ablation involves the destruction of tissue, leading to multiple complications. This ablation technique has been tried and tested; however, newer techniques are being investigated in order to avoid these complications. Pulsed field ablation, a nonthermal method of tissue ablation, is being explored as a more safe and efficient way to treat atrial fibrillation. This mini review aims to highlight the mechanisms of pulsed field ablation, its history and evolution, previous studies showing its efficacy, its major challenges and pitfalls, and future advancements to overcome these challenges. This method of ablation could potentially revolutionize the treatment of atrial fibrillation and prevent recurrences, thereby making it easier for the physicians and patients involved.